Pengamatan Karakteristik Schooling Ikan pada Area Bagan Tancap Sekitar Terumbu Karang dengan Teknologi Hidroakustik - Husni Angreni; Jumrawati Jumrawati; Ibnu Malkan Hasbi (Jurnal Airaha, 2020)
Fishing technology has always been developed to increase fishing productivity and more eco-friendly the environment. This study of fish schooling characteristics was conducted on a Fixed-Lift Net with LED lights using hydroacoustic method to determine the swimming activity of fish before midnight, at midnight, and after midnight. Experimental fishing method implemented by following fishing operations in the water of Pangkajene Kepulauan Regency in April to August 2019. The study showed that just before midnight, the fish in Fixed-Lift Net area tended to be at a depth 3-6 meters below the surface of the water and is dominated by the emergence of medium group and big group. At midnight the fish tend to be at a depth of 4-16 meters are dominated by the emergence of Small category fish (individually or solitary). Detection of fish in after midnight tends to be at a depth of 3-14 meters and is dominated by the appearance of medium group fish. Medium and large groups indicate large groups of fish. This can be used by fishermen to make the hauling process before and after midnight.